Examine the slide instead of just reading the report! - Luís Fernando Figueiredo Kopke; Aira Novello Vilar (Sociedade Brasileira de Dermatologia (SBD), 2024)
Histopathology reports are the pathologist's description of a microscopic morphological image, which can be understood as long as the basic elements of the histological structures are known. However, actually viewing the morphological image can be more helpful in understanding what is really being described, similar to the examination of radiograms, which is directly performed by the orthopedist despite the report being made by the radiologist. This article discusses this scenario, with the aim of encouraging surgeons to view and inspect morphological images to improve their understanding of the clinical-surgical status and their analysis of the state of the surgical margins or the histological subtype.